Penerapan Metode Bernyanyi Dalam Penguasaan Huruf Mudhoro’ah Fi’il Mudhori Melalui Google Classroom - sarah nur ulfa meilina (Taqdir, 2020)
Abstrac This research was conducted during the COVID-19 pandemic so that it was done online through Google Classroom application. The background of this research is the lack of the student’s ability to mastery modhoro’ah fi’il mudhori letters and the deficiency of method using in the learning activities so that the student tends to feel bored. The object of this research is the 2nd-grade student of MTs Al-Musyawarah Lembang. This research used a quasi-experiment method with a nonequivalent control group design. The results of the data analysis are: (1) The pre-test average value of the experiment class is 54.7, while the control class is 66.7. (2) After the treatment, the post-test average mark of the experiment test is 77.3, while the control class is 70. (3) The result of the N-Gain Score test after the use of the singing method on the experiment class is 50.5% that is categorized as Average, while the control class is 5.5% categorized as Low. This research concludes that the use of the singing method is quite a success to improve the ability of students to master the mudhoro’ah fi’il mudhori letters. Keywords: Mudhoro’ah Fi’il Mudhori Letters, Singing Method, Mastery.